Quadruple Helix Model in the Development of Halal Micro Business in North Sumatra - Muhammad Arif; Mustapa Khamal Rokan; Rahima Kumala (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2023)
This research explores stakeholder synergies in the development of halal micro-businesses in North Sumatra, Indonesia, focusing on the traditional Dodol business in Tanjung Pura, Langkat Regency. Using a qualitative, phenomenological approach, the study investigates stakeholders' perspectives within the Quadruple Helix model (Academics, Business Sector, Communities, Government), emphasizing the integration of Islamic banking. The findings reveal a lack of synergy among stakeholders due to differing visions, insufficient collective commitment and coordination, and limited financial support from banking institutions. Consequently, these factors have contributed to a discernible deceleration in the business's overall progress. Theoretically, key success factors in business development encompass shared mission, collective commitment, effective stakeholder coordination, and support from financial institutions. These empirical insights hold substantial significance, providing valuable guidance for governmental entities in formulating strategic approaches and implementing requisite support mechanisms to foster the growth and development of the Dodol business. Such support entails streamlining administrative procedures for small and medium-sized enterprises (SMEs), fostering collaborative partnerships with Islamic banks, optimizing business licensing processes, and facilitating the establishment of SME clusters to enhance financing opportunities for Dodol entrepreneurs.======================================================================================================== ABSTRAK – Model Quadruple Helix dalam Pengembangan Usaha Mikro Halal di Sumatera Utara. Penelitian ini bertujuan untuk menganalisis sinergisitas pemangku kepentingan dalam pengembangan usaha mikro halal di Sumatera Utara, Indonesia, dengan fokus pada usaha tradisional Dodol di Tanjung Pura, Kabupaten Langkat. Dengan pendekatan kualitatif fenomenologi, studi ini mengeksplorasi perspektif para pemangku kepentingan dalam kerangka Quadruple Helix (Akademisi, Sektor Bisnis, Komunitas, dan Pemerintah), dengan penekanan pada integrasi perbankan syariah. Temuan menunjukkan adanya kekurangsinergian diantara para pemangku kepentingan akibat adanya perbedaan visi, kurangnya komitmen kolektif dan koordinasi antar pemangku kepentingan, dan kurangnya dukungan pendanaan dari perbankan. Hal ini kemudian berdampak pada perlambatan perkembangan usaha ini. Secara teori, diantara faktor kunci kesuksesan dalam pengembangan suatu usaha adalah misi bersama, komitmen kolektif, koordinasi yang efektif para pemangku kepentingan, dan dukungan lembaga perbankan. Temuan ini berkontribusi dalam membahani entitas pemerintah terhadap bentuk-bentuk dukungan dalam pengembangan usaha Dodol ini. Dukungan tersebut meliputi penyederhanaan prosedur administratif untuk usaha mikro dan kecil (UMKM), memfasilitasi kemitraan kolaboratif dengan bank syariah, mengoptimalkan proses perizinan usaha, dan memfasilitasi pembentukan kelompok UMKM guna meningkatkan akses pembiayaan bagi para pengusaha Dodol.